Genetic characterization and phylogenetic analysis of the Nigella sativa (black seed) plastome - Lubna; Sajjad Asaf; Ibrahim Khan; Rahmatullah Jan; Saleem Asif; Saqib Bilal; Kyung-Min Kim; Ahmed AL-Harrasi (Scientific Reports, 2024)
Abstract In this study, the complete plastome sequence of Nigella sativa (black seed), was analyzed for the first time. The plastome spans approximately 154,120 bp, comprising four sections: the Large Single-Copy (LSC) (85,538 bp), the Small Single-Copy (SSC) (17,984 bp), and two Inverted Repeat (IR) regions (25,299 bp). A comparative study of N. sativa’s plastome with ten other species from various genera in the Ranunculaceae family reveals substantial structural variations. The contraction of the inverted repeat region in N. sativa influences the boundaries of single-copy regions, resulting in a shorter plastome size than other species. When comparing the plastome of N. sativa with those of its related species, significant divergence is observed, particularly except for N. damascena. Among these, the plastome of A. glaucifolium displays the highest average pairwise sequence divergence (0.2851) with N. sativa, followed by A. raddeana (0.2290) and A. coerulea (0.1222). Furthermore, the study identified 12 distinct hotspot regions characterized by elevated Pi values (> 0.1). These regions include trnH-GUG-psbA, matK-trnQ-UUG, psbK-trnR-UCU, atpF-atpI, rpoB-psbD, ycf3-ndhJ, ndhC-cemA, petA-psaJ, trnN-GUU-ndhF, trnV-GAC-rps12, ycf2-trnI-CAU, and ndhA-ycf1. Approximately, 24 tandem and 48 palindromic and forward repeats were detected in N. sativa plastome. The analysis revealed 32 microsatellites with the majority being mononucleotide repeats. In the N. sativa plastome, phenylalanine had the highest number of codons (1982 codons), while alanine was the least common amino acid with 260 codons. A phylogenetic tree, constructed using protein-coding genes, revealed a distinct monophyletic clade comprising N. sativa and N. damascene, closely aligned with the Cimicifugeae tribe and exhibiting robust support. This plastome provides valuable genetic information for precise species identification, phylogenetic resolution, and evolutionary studies of N. sativa.